Design and Fabrication of Si-HDPE Hybrid Fresnel Lenses for Infrared Imaging Systems - Ahmad Rosli, Abdul Manaf; Sugiyama, Tsunetoshi; Yan, Jiwang (Optical Society of America, 2017)
In this work, novel hybrid Fresnel lenses for infrared (IR) optical applications were designed and fabricated. The Fresnel structures were replicated from an ultraprecision diamond-turned aluminum mold to an extremely thin layer (tens of microns) of high-density polyethylene polymer, which was directly bonded onto a flat single-crystal silicon wafer by press molding without using adhesives. Night mode imaging results showed that the fabricated lenses were able to visualize objects in dark fields with acceptable image quality. The capability of the lenses for thermography imaging was also demonstrated. This research provides a cost-effective method for fabricating ultrathin IR optical components.